Wasathiyyah and Liberation Theology: A Comparative Analysis of Women’s Public Roles in the Thought of Yusuf Al-Qardawi and Asghar Ali Engineer - Qurrotul A’yuni; Istiadah Istiadah; Jamilah Jamilah (al-Afkar, Journal For Islamic Studies, 2026)
The discourse on women's public roles in Islam is often trapped in a polarization between patriarchal classical interpretations and contemporary feminist critiques. This study aims to analytically compare the thoughts of two prominent Muslim intellectuals, Yusuf al-Qardawi and Asghar Ali Engineer, regarding the legitimacy of women's participation in the public sphere. Utilizing a qualitative research method through library research and a comparative content analysis model, this study dissects the primary works of both figures as the basis for analysis. The findings indicate that both al-Qardawi and Engineer share a similar commitment to supporting women's public rights through a reinterpretation of texts responsive to modern changes. However, a significant methodological divergence exists. Al-Qardawi employs a wasathiyyah (moderate) approach based on maqasid al-shari’ah that maintains the authority of the usul fikih tradition, while Engineer applies a critical-contextual hermeneutics that deconstructs the text through the lens of historical materialism and liberation theology.